A world-leading sporting nation? An analysis of short- and long-term elite sport policy strategies in the UK - Yamamoto, M. (Japanese Journal of Elite Sports Support, 2008)
This article examines the development of elite sport policy in the UK in the last 10 years. It analyzes the way values and characteristics of elite sport changed, particularly after the 2012 Olympics was bestowed to London in July 2005. The analysis mainly draws on the extensive reviews of policy documents. Conflicting objectives are emerging that are between a short-term requirements for medals from the London 2012 Games and a long-term vision for the 'transformation of high performance system' in the UK.